Mengilhami Reformasi Pastoral Charles Borromeo dalam Praktik Pastoral di Era Digital - Raimundus Awur; Oktovianus Son; Krisanto Lafu Babu (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
Inspiring means providing encouragement or motivation for someone to think, create, or take action. This word is often used to describe a positive influence that drives creativity, ideas, or motivation in actions. For example, a work of art or noble deed can "inspire" others to create or act similarly. The focus of this article is to critically assess the theological meaning of pastoral ministry in the digital age. The article aims to provide a theological introduction to pastoral practices based on reformers’ views. Charles Borromeo, a figure influential in pastoral reform in the Church, is the role model or inspiration for this study. Using the historical theological reflection method, the contributions of pastoral practices from the Reformation era are compared with those of the digital age. The research method is qualitative, descriptive, and historical, and it involves literature review on relevant topics. This study is motivated by a decline in contextual pastoral spirit, aiming to discover new methods or innovations in pastoral reform.